2020
DOI: 10.1371/journal.pgen.1009268
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the Plasmodium falciparum GTP-cyclohydrolase 1, dihydrofolate reductase and dihydropteroate synthetase genes reveals new insights into sulfadoxine-pyrimethamine antimalarial drug resistance

Abstract: Plasmodium falciparum parasites resistant to antimalarial treatments have hindered malaria disease control. Sulfadoxine-pyrimethamine (SP) was used globally as a first-line treatment for malaria after wide-spread resistance to chloroquine emerged and, although replaced by artemisinin combinations, is currently used as intermittent preventive treatment of malaria in pregnancy and in young children as part of seasonal malaria chemoprophylaxis in sub-Saharan Africa. The emergence of SP-resistant parasites has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…The most likely first step was single mutation A437G, in agreement with previous studies which found A437G was the most frequent single mutation sulfadoxine-resistant Pf DHPS isolates [13, 47] and the data presented in [46]. Furthermore, A437G is now considered fixed in the population [48] and A437G is also the most common mutation in our isolate data, followed by S436A (Figure 5b). The most likely double mutation in our simulations was A437G/S436A, followed by A437G/K540E.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The most likely first step was single mutation A437G, in agreement with previous studies which found A437G was the most frequent single mutation sulfadoxine-resistant Pf DHPS isolates [13, 47] and the data presented in [46]. Furthermore, A437G is now considered fixed in the population [48] and A437G is also the most common mutation in our isolate data, followed by S436A (Figure 5b). The most likely double mutation in our simulations was A437G/S436A, followed by A437G/K540E.…”
Section: Resultssupporting
confidence: 91%
“…Plasmodium falciparum and vivax SNP data were sourced from recent studies [45, 48]. In those studies, paired Illumina raw sequence data was mapped to the Pf3D7 (P. falciparum) or PVP01 ( P. vivax ) reference genome using bwa-mem software (default parameters).…”
Section: Methodsmentioning
confidence: 99%
“…However, given their close geographical proximity and the continuous movement of people between these sites, the culturing of some isolates prior to sequencing may be confounding these results 29 . The Pfdhps gene, known to be associated with resistance to SP, was found to be in the top 5% of IBD positions in island isolates from Lake Victoria, suggesting this gene is being highly conserved in this population, likely due to the continued use of SP as a method of intermittent preventative treatment in pregnancy (IPTp) 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…SMC may reduce the incidence in untreated age groups ( Cisse et al, 2016 ), suggesting an interruption of transmission. There is some evidence to suggest that SMC can increase the prevalence of drug resistance markers for pfdhps and pfdhfr ( Access-SMC-Partnership, 2020 ; Dieng et al, 2019 ; Maiga et al, 2016 ; Some et al, 2014 ; Turkiewicz et al, 2020 ). These data suggest that monitoring for resistance is an important consideration with repeated use of SMC.…”
Section: Impact and Consequences Of Population-level Drug-based Interventions: Smc Mdamentioning
confidence: 99%